Posterior urethral valves: Morphological normalization of posterior urethra after fulguration is a significant factor in prognosis - Menon Prema; Rao K. L. N.; Vijaymahantesh S; Kanojia R; Samujh R; Batra Y; Sodhi K; Saxena A; Bhattacharya A; Mittal B (Wolters Kluwer Medknow Publications, 2010)
Aim: To assess the changes in urethral morphology 3 months post fulguration of posterior urethral valves (PUVs) on micturating cystourethrogram (MCUG) and correlate these changes with the overall clinical status of the patient. Materials and Methods: A total of 217 children, managed for PUVs during a period of 6 years in a single surgical unit were prospectively studied. The ratio of the diameters of the prostatic and bulbar urethras (PU/BU) was calculated on the pre- and post-fulguration MCUG films. They were categorized into three groups based on the degree of normalization of posterior urethra (post-fulguration PU/BU ratio). Results: Group A: Of the 133 patients, 131 had normal urinary stream and 4 (3%) had nocturnal enuresis. Vesicoureteral reflux (VUR), initially seen in 83 units (31% units), regressed completely at a mean duration of 6 months in 41 units (49%). Of the 152 non-VUR, hydroureteronephrosis (HUN) units, 11 were poorly functioning kidneys. Persistent slow but unobstructed drainage was seen in 23 units (16%) over a period of 1.5-5 years (mean 2.5 years). Group B: All the 11 patients had a normal stream. Four (36.4%) had daytime frequency for a mean duration of 1 year and one (9%) had nocturnal enuresis for 1 year. Grade IV-V VUR was seen in five patients (three bilateral), which regressed completely by 3 months in five units (62.5%). In the non-VUR, HUN patients, slow (but unobstructed) drainage was persistent in two units (14%) at 3 years. Group C: Of the 16 patients, only 5 (31.3%) were asymptomatic. Six patients (nine units) had persistent VUR for 6 months to 3 years. Of the 20 units with HUN, 17 (85%) were persistent at 1-4 years (mean 2 years). Eight patients (50%) required a second fulguration while 3 (18.7%) required urethral dilatation for stricture following which all parameters improved. Conclusions: Adequacy of fulguration should be assessed by a properly performed MCUG. A postop PU/BU ratio >3 SD (1.92) should alert to an incomplete fulguration or stricture. Patients within normal range ratio have faster recovery of slow draining units, reflux and less voiding dysfunction. There is a strong correlation between incomplete fulguration and persistent slow draining units, uremia, voiding dysfunction and urinary tract infections.